The Influence of Green Marketing and Green Awareness on Green Attitudinal Loyalty at Luxury Brand Pramana - Weda, Ni Putu Risa Sasikirana; Witarsana, I Gusti Agung Gede; Suastini, Ni Made (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to examine the contribution of green marketing and green awareness to green attitudinal loyalty. This community service targets people who have stayed at Luxury Brand Pramana, with a sample of 100 respondents. The methods used include Multiple Linear Regression, Coefficient of Determination, t-test, and F-test. The research process was carried out over a period of 6 months starting from December 2023 to May 2024. The results of the study showed that green marketing and green awareness, both individually and together, have a significant effect on green attitudinal loyalty with an effect of 58.8%. The implication is that Luxury Brand Pramana is expected to increase promotion through advertising and social media with environmental messages, consistently apply environmentally friendly concepts, and adjust pricing policies.